Screening and identification of lipolytic potential of Actinobacteria from cemetery in Bonoloyo, Surakarta, Central Java, Indonesia - ALDEN GANENDRA MADHAVA PRIYA HARDIANTO; TRIASTUTI RAHAYU; ERMA MUSBITA TYASTUTI; LINA AGUSTINA; NOOR ALIS SETIYADI; YASIR SIDIQ (Society for Indonesian Biodiversity, 2025)
Abstract. Hardianto AGMP, Rahayu T, Tyastuti EM, Agustina L, Setiyadi NA, Sidiq Y. 2025. Screening and identification of lipolytic potential of Actinobacteria from cemetery in Bonoloyo, Surakarta, Central Java, Indonesia. Biodiversitas 26: 2786-2793. Cemetery soil is a unique reservoir of Actinobacteria with a significant lipolytic potential, in which lipids are 12.51-23.60% of the human body, a fact that has been largely overlooked in previous studies. However, studies on this subject are limited. This study, therefore, aimed to assess the lipolytic potential of 29 isolates from the Actinobacteria collection and to characterize the selected isolates further. Lipolytic screening was conducted on Tributyrin Agar (TBA) media for 72 hours, and the potential was determined by Lipolytic Index (LI). Subsequently, the colony morphology and spore type of the selected isolates were characterized through binocular microscopy and Scanning Electron Microscope (SEM). Identification was further conducted based on the 16S rRNA gene. These results showed that almost all tested isolates possess lipolytic ability, with the highest LI of 3.18 (T22). In general, the lipolytic potential of Actinobacteria was found to increase gradually after up to 72 hours of incubation. The aerial and vegetative mycelia were T5 for white and T22 for yellow, respectively, with closed spiral spores. Molecular identification showed that the T22 isolate is closely related to the Streptomyces sp. strain GSENDO-0580, with 99.93% similarity. In conclusion, this research underscores the urgent need for an in-depth study of Streptomyces sp. strain GSENDO-0580 is urgently needed, considering the extensive application of lipase enzymes in various fields.